2018
DOI: 10.1002/gdj3.55
|View full text |Cite
|
Sign up to set email alerts
|

The MaRIUS‐G2G datasets: Grid‐to‐Grid model estimates of flow and soil moisture for Great Britain using observed and climate model driving data

Abstract: The MaRIUS‐G2G datasets were produced for the MaRIUS (Managing the Risks, Impacts and Uncertainties of drought and water Scarcity) project, using the Grid‐to‐Grid (G2G) national‐scale hydrological model for Great Britain. There are six separate datasets, with each of three combinations of meteorological driving data (two observation‐based and one from climate model ensembles) used to produce two types of outputs (daily time‐series of natural river flow for 260 sites, and monthly 1 × 1 km grids of natural flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Mean bias (model-Obs) and Nash-Sutcliffe efficiency metrics, computed from 1 December 2013, are listed. River flows from the G2G in dark blue(Bell et al, 2018) and DECIPHeR in grey(Coxon et al, 2019b) hydrological models driven by the same observed precipitation and observation-based potential evaporation are also shown as a reference. As DECIPHeR is a 100-member ensemble dataset, the ensemble mean is plotted along with maxima and minima simulated daily flows F I G U R E 9 Timeseries of accumulated discharge from land to ocean around England, Scotland and Wales coastlines during winter 2013/14 in the CPL simulations (red), as assumed in the AMM15 ocean model climatology (blue) and a UK National Runoff Series estimated from gauge observations by the National River Flow Archive (black dashed line;Marsh et al, 2015) December/January peak and, consistent with Figure8, show less dayto-day variability than the UKNRS reference.…”
mentioning
confidence: 99%
“…Mean bias (model-Obs) and Nash-Sutcliffe efficiency metrics, computed from 1 December 2013, are listed. River flows from the G2G in dark blue(Bell et al, 2018) and DECIPHeR in grey(Coxon et al, 2019b) hydrological models driven by the same observed precipitation and observation-based potential evaporation are also shown as a reference. As DECIPHeR is a 100-member ensemble dataset, the ensemble mean is plotted along with maxima and minima simulated daily flows F I G U R E 9 Timeseries of accumulated discharge from land to ocean around England, Scotland and Wales coastlines during winter 2013/14 in the CPL simulations (red), as assumed in the AMM15 ocean model climatology (blue) and a UK National Runoff Series estimated from gauge observations by the National River Flow Archive (black dashed line;Marsh et al, 2015) December/January peak and, consistent with Figure8, show less dayto-day variability than the UKNRS reference.…”
mentioning
confidence: 99%
“…The weather@home2 climate ensemble (Guillod et al, ) has been used to drive the national Grid‐to‐Grid (G2G) hydrological model (Bell et al, ) to provide simulated daily river flows for the baseline, near future, and far future periods (Bell, Kay, et al, ; Bell, Rudd, et al, ). For each period, 100 simulations of daily mean river flow for each of 129 catchments across England and Wales have been used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…As an input, G2G requires time series of precipitation and potential evaporation (PE), driven by the above-mentioned hydro-meteorological time series data. As an output G2G provides monthly averages of daily mean soil moisture (m 3 ) for the 1975-2004 baseline time-period, and for each of the 100 simulations (Bell et al, 2018a(Bell et al, , 2018b). In the first two years of the baseline data simulation G2G was being "spun up" (Bell et al, 2018a) so soil moisture estimates for the first two years are ignored and all results presented here reflect the simulated baseline period 1977-2004.…”
Section: Estimating Restrictions On Green Watermentioning
confidence: 99%
“…These include the weather@home2 sequences (Guillod et al., 2018), which can be downloaded from the Centre for Environmental Data Analysis (CEDA) repository at http://catalogue.ceda.ac.uk/uuid/0cea8d7aca57427fae92241348ae9b03. The Grid‐to‐Grid model estimates of monthly mean flow and soil moisture for Great Britain (Bell et al., 2018b), which can be downloaded from the NERC Environmental Information Data Centre repository at https://doi.org/10.5285/3b90962e-6fc8-4251-853e-b9683e37f790. The Water Resource England and Wales (WREW) model cannot be shared due to security reasons.…”
Section: Data Availability Statementmentioning
confidence: 99%